Location Based MAC Protocol with Directional Antennas for Multi hop Wireless Networks - Chekol, Solomon Gebre (The Graduate School, Ajou University, 2013)
In multi hop wireless networks environment destination node is situated at distance of multiple hops far away from source node. Existing MAC schemes in multi hop wireless Networks (MWN) suffer from large end-to-end packet delay, interference, inefficient channel utilization, and degraded throughput. In this thesis work we propose a MAC scheme that overcomes the limitations of current MAC protocols in MWN and uses directional antenna for data packet transmission and Omni antenna for control packet transmission. The proposed MAC scheme classified as scheme-I that first reserves channel before data packets are transmitted directionally, and scheme-II that uses pipelined approach and overlaps the Omni directionally transmitted control packets and directionally transmitted data packets in time. Our proposed MAC scheme handles hidden terminal problem and related packet collision in MWN environment by employing M-RTS/M-CTS which is extended version of ordinary CSMA/CA RTS/CTS packets to inform other neighbors to refrain from harming the ongoing transmissions.
학위논문(석사)아주대학교 일반대학원 :컴퓨터공학과,2013. 8